The monotypic genus Nephelobotys Munroe & Mutuura, 1970 (Lepidoptera, Crambidae, Pyraustinae): two new species from Laos and a newly combined species from Korea - Ko, Jae-Ho; Bayarsaikhan, Ulziijargal; Lee, Tak-Gi; Bae, Yang-Seop (Zootaxa, 2022)
The genus Nephelobotys is newly recorded from Laos and two new species Nephelobotys denticulatus sp. nov. and Nephelobotys forcipatus sp. nov. are newly described. Nephelobotys evenoralis (Walker, 1859) comb. nov., is also newly reported from Korea. Illustrations of adults and genitalia are provided. The differences with related genus Torulisquama Zhang & Li, 2010 are briefly discussed.